2021
DOI: 10.1186/s43141-021-00216-0
|View full text |Cite
|
Sign up to set email alerts
|

Narrative role of vitamin D receptor with osteoporosis and obesity in a sample of Egyptian females: a pilot study

Abstract: Background Vitamin D receptor (VDR) is known as one of the cellular regulators for several metabolic pathways indicating its pivotal role in the pathological pathway of numerous diseases. Considering the high frequency of osteoporosis and obesity among women, the current study aimed to explore the prospective assembly of the most frequent two VDR loci, single nucleotide polymorphism SNPs rs731236 (TaqI) and rs7975232 (ApaI) with a genetic predisposition to osteoporosis (skeletal) and obesity (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…The SNP rs7975232 is located in the 3 -regulatory region of the VDR gene. The latest study reported an association of rs7975232 homozygous genotype with osteoporosis risk in Egyptian women [43]. This contrasts our study which found heterozygous genotype (AC) of rs7975232 to be associated with increased odds of having PMO as compared to the homozygous genotype (AA).…”
Section: Discussioncontrasting
confidence: 99%
“…The SNP rs7975232 is located in the 3 -regulatory region of the VDR gene. The latest study reported an association of rs7975232 homozygous genotype with osteoporosis risk in Egyptian women [43]. This contrasts our study which found heterozygous genotype (AC) of rs7975232 to be associated with increased odds of having PMO as compared to the homozygous genotype (AA).…”
Section: Discussioncontrasting
confidence: 99%